2021
DOI: 10.1016/j.asmr.2020.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Publicly Available Rehabilitation Protocols Designated for Meniscal Repairs Are Highly Variable

Abstract: Purpose: To compare publicly available rehabilitation protocols designated for meniscal repairs published online to determine the variability in meniscus repair protocols including different types of tears (radial vs nonradial repairs). Methods: From the Fellowship and Residency Electronic Interactive Database Access System (FREIDA), a list of publicly available academic residency programs and orthopaedic sports medicine fellowships was obtained. With this list, an electronic search using Google was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This technique allows an anatomic repair and does not change the meniscus physiological properties after a posterior horn lesion [31]. The literature shows little agreement on guidelines on rehabilitation after meniscal repair [12, 23, 54, 67]. Weight‐bearing was not allowed in four of the included studies for the first 2–6 weeks [13, 38, 51, 68].…”
Section: Discussionmentioning
confidence: 99%
“…This technique allows an anatomic repair and does not change the meniscus physiological properties after a posterior horn lesion [31]. The literature shows little agreement on guidelines on rehabilitation after meniscal repair [12, 23, 54, 67]. Weight‐bearing was not allowed in four of the included studies for the first 2–6 weeks [13, 38, 51, 68].…”
Section: Discussionmentioning
confidence: 99%
“…Our rehabilitation protocols, differentiated by meniscal tear stability, were designed based on evidence suggesting varied recovery trajectories [15][16][17][18][19]. Each protocol aims to optimize recovery while mitigating risk of reinjury.…”
Section: Rehabilitation Protocolmentioning
confidence: 99%
“…Therefore, previous study has shown varied recovery trajectories based on the type of meniscal tear, highlighting the need for tailored rehabilitation approaches [15]. Furthermore, in several previous studies [15][16][17], there was a difference in rehabilitation programs, including ROM, WB, and muscle strengthening after surgery in patients with stable and unstable meniscal tears; in particular, restricted rehabilitation was recommended after meniscal repair for unstable meniscal tears [16][17][18]. Differences in rehabilitation methods, especially restricted rehabilitation, may affect the recovery of functional outcomes after surgery.…”
Section: Introductionmentioning
confidence: 98%